IMPROVING LEARNING OUTCOMES OF BASIC ACCOUNTING IN X GRADERS THROUGHT COOPERATIVE LEARNING MODELS IN JIGSAW TYPE - Risa Novita Wati; Adeng Pustikaningsih (Universitas Negeri Yogyakarta, 2019)
This study aims to: find out the differences in learning outcomes of Basic Accounting in X Graders at SMK Negeri 1 Depok Academic Year 2018/2019 before and after the application of the Jigsaw Cooperative Learning Models. This research is a Quasi-Experimental study. Data collection techniques using simple random sampling for the selection of control classes and experimental classes that will be drawn randomly. The subjects of this study were students of class X AKL 1 and X AKL 3 at SMK Negeri 1 Depok. The design of data collection in this study uses the Pretest-posttest control group design model. Data analysis was performed using descriptive analysis and hypothesis testing. The results of the study are: (1) the pre-test learning outcomes in the control class obtained an average value of 71.376, the highest value of 90 and the lowest value of 50. While the pre-test scores in the experiment class obtained an average value of 71.8, the highest value of 90 and the lowest value of 50 (2) post-test learning outcomes in the control class obtained an average value of 71.433, the highest value of 83 and the lowest value of 60. While the post-test in the experiment class obtained an average of 80.733 with the highest value of 90 and the lowest value of 67. (3) Based on the results of the t-test that is 6.122 ≥ 2.00172 or tcount ttable on the results of the post-test of the experiment group and the control group, it can be concluded that there are significant differences between the results of the control class and the experiment class so that there is a significant increase the application of Cooperative Learning Models in Jigsaw type in Basic Accounting subjects to the learning outcomes of X Accounting Graders. Keywords: Jigsaw, Learning Outcomes, Basic Accounting